ARCHITECTURE OF UNIVERSITY EDUCATIONAL PROCESSES IN THE CONDITIONS OF THE COVID-19 PANDEMIC: FROM SMALL DATA TO BIG DATA AND DATA SCIENCE - Ershova, Inna Vladimirovna; Enkova, Ekaterina Evgenievna; Laptev, Vasily Andreevich; Petrakov, Andrey Yurievich (International Journal of Law in Changing World, 2025)
The paper focuses on the degree of influence of Big Data on building the educational process at the Russian Law University during the COVID-19 pandemic. We use the sociological method as the primary research method. The result shows the influence of the collected information on administrative decision-making. Additionally, we describe the educational process within the selected university. The paper demonstrates student attitude toward Big Data in various aspects, including awareness of the technology and its significance for the university's management. We conclude that Big Data has not yet been widely used in Russian higher education. Therefore, we identify the reasons preventing the use of Big Data in education. This research novelty lies in pointing to Big Data's impact on the architecture of the university educational process in different periods of the COVID-19 pandemic when higher education institutions implemented distance or mixed learning and online communications. ______ ARQUITECTURA DE LOS PROCESOS EDUCATIVOS UNIVERSITARIOS EN LAS CONDICIONES DE LA PANDEMIA DE LA COVID-19: DEL SMALL DATA AL BIG DATA Y LA CIENCIA DE DATOS El documento se centra en el grado de influencia de Big Data en la construcción del proceso educativo en la Universidad de Derecho de Rusia durante la pandemia de COVID-19. Utilizamos el método sociológico como el principal método de investigación. El resultado muestra la influencia de la información recopilada en la toma de decisiones administrativas. Además, describimos el proceso educativo dentro de la universidad seleccionada. El documento demuestra la actitud de los estudiantes hacia Big Data en varios aspectos, incluido el conocimiento de la tecnología y su importancia para la gestión de la universidad. Concluimos que Big Data aún no se ha utilizado ampliamente en la educación superior rusa. Por lo tanto, identificamos las razones que impiden el uso de Big Data en educación. Esta novedad de la investigación radica en señalar el impacto de Big Data en la arquitectura del proceso educativo universitario en diferentes períodos de la pandemia de COVID-19 cuando las instituciones de educación superior implementaron aprendizaje a distancia o mixto y comunicaciones en línea. ______ 新冠疫情条件下的大学教育流程架构：从小数据到大数据和数据科学 本文重点研究了大数据在COVID-19大流行期间对俄罗斯法学院教育流程构建的影响程度。我们以社会学方法作为主要研究方法。结果显示了收集到的信息对行政决策的影响。此外，我们还描述了所选大学内的教育过程。本文从各个方面展示了学生对大数据的态度，包括对该技术的认识及其对大学管理的意义。我们得出的结论是，大数据尚未在俄罗斯高等教育中得到广泛应用。因此，我们找出了阻碍大数据在教育中使用的原因。这项研究的新颖之处在于指出了大数据在COVID-19大流行的不同时期对大学教育过程架构的影响，当时高等教育机构实施了远程或混合学习和在线通信。